2017
DOI: 10.1001/jamapsychiatry.2017.2582
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Suicide Attempts Among Adults in the United States

Abstract: A recent overall increase in suicide attempts among adults in the United States has disproportionately affected younger adults with less formal education and those with antisocial personality disorder, anxiety disorders, depressive disorders, and a history of violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
148
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 52 publications
10
148
4
Order By: Relevance
“…Notwithstanding, we consider this possibility unlikely because there is no evidence of a contemporary decrease in suicidal behaviors either in Madrid or elsewhere in Spain. On the contrary, data from outpatient and inpatient facilities suggest a general increase in such behaviors, in line with what has been observed in several samples from the United States (Olfson, Blanco, et al., ; Wester, Trepal, & King, ). A study conducted in Andalusia, Spain, analyzed data on suicide attempts using telephone call records from the public emergency health care system: They found that the number and rate of attempts increased annually between 2010 and 2013, the last year of study (Mejías‐Martín et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…Notwithstanding, we consider this possibility unlikely because there is no evidence of a contemporary decrease in suicidal behaviors either in Madrid or elsewhere in Spain. On the contrary, data from outpatient and inpatient facilities suggest a general increase in such behaviors, in line with what has been observed in several samples from the United States (Olfson, Blanco, et al., ; Wester, Trepal, & King, ). A study conducted in Andalusia, Spain, analyzed data on suicide attempts using telephone call records from the public emergency health care system: They found that the number and rate of attempts increased annually between 2010 and 2013, the last year of study (Mejías‐Martín et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…Many reasons are provided in the literature for the high rates of suicide in military populations. In civilian populations, risk factors for suicide and suicidal thoughts vary and include depression, post-traumatic stress disorder, anxiety, economic challenges, lower levels of education, antisocial personality disorder, borderline personality disorder, substance use disorders, not being in a stable relationship, low levels of social support, and a history of violent behavior (Gunnell, Harbord, Singleton, Jenkins, & Lewis, 2004;Olfson et al, 2017). In military-connected populations, similar reasons account for higher suicide rates including economic issues, underlying mental health difficulties (post-traumatic stress disorder and depression in particular), relationship problems, and an accumulation of life stressors (Franklin, 2016;Griffith, 2012Griffith, , 2017Office of Suicide Prevention, 2016).…”
Section: Suicide In Military Populationsmentioning
confidence: 99%
“…One study of National Guard members, shortly after return from deployment, showed that up to 40% of National Guard members met the criteria for one or more of the following mental health difficulties: post-traumatic stress disorder (PTSD), depression, suicide ideation, and hazardous alcohol use (Gorman et al, 2011). Although anxious/agitated disorders such as PTSD are related to the transition from suicide ideation to attempt (Nock, Hwang, Sampson, & Kessler, 2010;Nock et al, 2009), many National Guard members experience a variety of barriers to mental health care, including a lack of nearby services, stigma surrounding treatment, and fear of career repercussions (Valenstein et al, 2014). These barriers can prevent National Guard service members from receiving the treatment they need and consequently put them at higher risk for suicide.…”
Section: Suicide In Military Populationsmentioning
confidence: 99%
See 2 more Smart Citations